A Novel Case of Resolved Postherpetic Neuralgia with Subsequent Development of Trigeminal Neuralgia: A Case Report and Review of the Literature. (30th July 2013) - Mason, Alexander; Ayres, Kristen; Burneikiene, Sigita; Villavicencio, Alan T.; Nelson, E. Lee; Rajpal, Sharad
Abstract : A 72-year-old female patient is presented, who was diagnosed with herpes zoster along the left ophthalmic branch of the trigeminal nerve with associated cutaneous vesicles. The patient subsequently developed postherpetic neuralgia in the same dermatome, which, after remission, transformed into paroxysmal trigeminal pain. The two different symptom sets, with the former consistent with PHN and the later consistent with trigeminal neuralgia, were unique to our practice and the literature.